Nursing research using life history : qualitative designs and methods in nursing - De Chesnay, Mary (Qualitative designs and methods in nursing., 2015)
Of the LiteratureAreas of Agreement; Areas of Disagreement; Deficiencies in the Existing Research; Research Questions; Methodology; Sample; Life History Design; The Researcher as Instrument; Interview Guide; Conduct of Interviews; Human Subjects Approval; Setting; Transcriptionists; Data Analysis; Results; Summary of Themes; The Stories; Key Informant #1: Allyson; Key Informant #2: Becky; Themes and Subthemes; Theme #1: Coping; Theme #2: Self-Image; Theme #3: Communication Barriers; Theme #4: Communication Facilitators; Discussion; Whistleblowing in Small Organizations.